Faktor-faktor yang mempengaruhi keputusan wanita bekerja untuk berbelanja di supermarket Kota Surabaya - Sularso, Andi (Akutansi Bisnis & Manajemen ( ABM ), 2004)
Dari search is I Made at determining the factor stimulus marketing customers decision of to shop at supermarket in Surabaya city in this Resort the target responden is female worker up 150 selected diary education, purposive random sampling was up pb Lite. Teoretical analisis indikatif that the 33 faktor the image of the stimulus marketings search has product, price, promotion, service, atribut and location to the image of retail bisnis (supermarket). Where determinate and by appleying Factor analysis statistikal where 8.00 rilis faktor, home 33 variabel pintu 8 tutup inti variabel with eigen value 1 n varian komulatif value of 59,93% or 60,00% titik this research indicated that 8 faktor Tekken into account to come to Desi Yen to buy at supermarket according to priority atribut physical supermarket faktor tukang to one day on and that product